A randomised phase II trial of capecitabine plus cisplatin versus S-1 plus cisplatin as a first-line treatment for advanced gastric cancer: Capecitabine plus cisplatin ascertainment versus S-1 plus cisplatin randomised PII trial (XParTS II). (September 2018) - Nishikawa, Kazuhiro; Tsuburaya, Akira; Yoshikawa, Takaki; Kobayashi, Michiya; Kawada, Junji; Fukushima, Ryoji; Matsui, Takanori; Tanabe, Kazuaki; Yamaguchi, Kazuya; Yoshino, Shigefumi; Takahashi, Masazumi; Hirabayashi, Naoki; et al.
Abstract: Background: Capecitabine plus cisplatin (XP) is a standard global regimen, while S-1 plus cisplatin (SP) is a Japanese standard for first-line treatment of advanced gastric cancer (AGC). We conducted a phase II trial comparing XP with SP for patients with AGC to confirm whether these regimens can be used as controls in a phase III study and to explore whether histological subtypes favour XP or SP. Patients and methods: Eligible patients were randomised to receive either S-1 40 mg/m 2 for 21 days plus cisplatin 60 mg/m 2 (q5w) or capecitabine 1000 mg/m 2 for 14 days plus cisplatin 80 mg/m 2 (q3w). The primary end-point was progression-free survival (PFS). The secondary end-points were overall survival (OS), overall response rate (ORR) and safety. Results: In 110 eligible patients, 24-week PFS was higher in both groups (SP 50.9%, XP 43.5%) than the protocol-specified threshold of 40%. The median PFS for SP versus XP was 5.6 and 5.1 months (hazard ratio [HR], 1.126; p = 0.5626); OS was 13.5 and 12.6 months (HR, 0.942; p = 0.7769) and the ORR was 42.4% and 69.4% ( p = 0.0237), respectively. The most common grade ≥3 adverse events with SP/XP were anaemia (16%/20%), neutropenia (9%/18%) and anorexia (18%/13%). Subgroup analysis by histological classification showed no statistical difference between treatments. Conclusions: XP and SP are comparable and can be recommended as control arms in a phase III study for AGC. Histological subtypes were not sensitive markers for the selection of XP or SP. Clinical trial registration: NCT00140624 . Highlights: Capecitabine plus cisplatin (XP) and S-1 plus cisplatin (SP) showed promising progression-free survival (PFS; 5.1 and 5.6 months). PFS of 24 weeks was higher in both groups than the protocol-specified threshold of 40%. XP and SP for first-line treatment of AGC was well tolerated and showed appropriate overall survival and overall response rate. Histological subtyping showed no survival difference between XP and SP. Histological subtypes were not sensitive markers for fluorouracil selection.